ANALISIS PEMUTUSAN HUBUNGAN KERJA AKIBAT MOGOK KERJA TIDAK SAH PADA PT SRIREJEKI PERDANA STEEL (STUDI KASUS: PUTUSAN PENYELESAIAN HUBUNGAN INDUSTRIAL NOMOR 74/G/2014/PHI-BDG JO PUTUSAN MAHKAMAH AGUNG NOMOR 58/K/PDT.SUS-PHI/2015)” - Jovania Hardisa; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2018)
Strike is a collective refusal by employees to work under the conditions required by employers. Strikes arise for a number of reasons, though principally in response to economic conditions or labor practices. However, in some cases, there is still no decidedly regulation that a strike can lead to the Termination of Employment. This paper will describe the case of 255 employees in PT Srirejeki Perdana Steel which being terminated by the employer of PT Srirejeki Perdana Steel without negotiation. Under the Law Number 13 of 2003 on Manpower, negotiation is an obligatory and essential material that must be done before the employer can terminate their workers. This paper will describe the completion of the right caused by the termination of 255 employees in PT Srirejeki Perdana Steel. The author research the problem with normative method supported by the interview of experts related to the case. There must be a proper regulation to fulfill the right of employee and law certainty to achieve justice for all.